Convex Optimization of Reliability and Cost for Reduction Oxygen Supply System of a Spacecraft via Dragonfly Algorithm - Fouad Hamza Abd Alsharify (Mathematical Statistician and Engineering Applications, 2022)
To optimize the reliability of the Reduction Oxygen Supply System of a Spacecraft, Dragonfly algorithm was used which simulates the swarming behavior of dragonflies. To find out the best reliability with the lowest cost, we used two different cost functions: logarithm and exponential functions with this algorithm. A comparison was made between the results of cost functions.